A comprehensive review of microplastic pollution in freshwater and marine environments - Irene Monica Jaikumar; Majesh Tomson; Arun Meyyazhagan; Balasubramanian Balamuralikrishnan; Rathinasamy Baskaran; Manikantan Pappuswamy; Hesam Kamyab; Elham Khalili; Mohammad Farajnezhad (Green Analytical Chemistry)
Water popularly termed the ‘The Elixir of Life’ is now polluted beyond control in several regions. Microplastics, the tiny contaminants have found their way into all walks of life. They have also been found to be present in human blood, multiple organs, and even breast milk. There is an abundance of microplastics in the air we breathe, the food we eat, and the water we drink. Curbing them has to start with a ban of all forms of primary microplastics, and single use plastics with preference being given to biodegradable alternatives. India in particular banned single use plastics in 2022, which put an end to several commonly used plastic items being replaced with biodegradables. Paint is one of the largest contributors to microplastics, followed by textile industry, cosmetic, pharmaceutical industry, packaging industry are all top contributors to microplastics. The wastewater treatment plants aren't designed to filter microplastics from the source and this results in microplastics polluting all water resources. Though several novel techniques for microplastic segregation exist such as sieving, filtration, density separation, visual sorting, alkali digestion exist, they aren't fully employed as the initial process of microplastic segregation from waste is still in question.